Tubal abnormalities on hysterosalphingography in primary and secondary infertility in Sokoto, Northwestern-Nigeria - Danfulani, M.; Yunusa, G. H.; Ma'aji, S. M.; Sa'idu, S. A.; Musa, M. A. (Asian Journal of Medical Sciences, 2014)
Background: Hysterosalphingography (HSG) remains a vital method of assessing tubal patency especially in a resource limited setting such as ours and tubal occlusion is the commonest cause of female infertility in the developing world. Objective: To review abnormal tubal pathological findings in hysterosalphingography (HSG) among women being investigated for primary and secondary infertility in Sokoto. Method: This is a retrospective review of HSG results of 317 women being investigated for both primary and secondary infertility was reviewed. The study was conducted from July 2009 to August 2012. Results: A total of 317 patients were studied. The age ranges of the study participants was from 17 - 48 years with a mean and standard deviation value of 32.5 ± 5.5. Out of the sample size, 139 (43.85%) showed normal HSG findings while 178 (56.15%) patients had abnormal HSG findings. Tubal abnormalities were found in 112 (35.33%) of the patients. The commonest tubal abnormality was tubal blockage. Conclusion: The high incidence of tubal pathology revealed in this study showed that HSG is still a very vital tool for infertility work-up. Early detection and prompt treatment of infection in our women should be encouraged as it is the major leading cause of tubal pathologies and consequently this would reduce the contribution of tubal infertility in this environment. DOI: http://dx.doi.org/10.3126/ajms.v6i2.10581 Asian Journal of Medical Sciences Vol.6(2) 2015 48-51